2019
DOI: 10.1111/cxo.12825
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival ultraviolet autofluorescence area, but not intensity, is associated with myopia

Abstract: Myopia was associated with smaller areas of CUVAF indicative of less cumulative ultraviolet-B exposure. These findings suggest that CUVAF measures are a useful, non-invasive biomarker of the time spent outdoors in adults in northern hemisphere populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 36 publications
(54 reference statements)
3
30
0
Order By: Relevance
“…There are a number of published clinical studies demonstrating ocular surface damage from natural UV exposure, mainly utilising the method of conjunctival UV autofluorescence (CUVAF) [12,[15][16][17], which has been proposed as a biomarker for time spent outdoors [17]. Interestingly, there are limited publications on eye protection during suntanning sessions, and no published clinical studies evaluating the damage of the ocular surface during artificial indoor suntanning [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of published clinical studies demonstrating ocular surface damage from natural UV exposure, mainly utilising the method of conjunctival UV autofluorescence (CUVAF) [12,[15][16][17], which has been proposed as a biomarker for time spent outdoors [17]. Interestingly, there are limited publications on eye protection during suntanning sessions, and no published clinical studies evaluating the damage of the ocular surface during artificial indoor suntanning [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The subjective and retrospective nature of the questionnaire used to obtain information could explain the absence of significant differences between the groups. Therefore, more objective methods should be implemented in future studies, for example biomarkers of outdoor exposure such as vitamin D levels [44] or conjunctival ultraviolet autofluorescence [45][46][47][48][49].…”
Section: Plos Onementioning
confidence: 99%
“…Several previous cross-sectional studies have found an inverse association between the serum concentration of 25[OH]D and measures of myopia in children and young adults 11,12,17,18. On the other hand, a small ( n = 50) cross-sectional study of young adults in Northern Ireland recently found no significant difference in 25[OH]D 3 concentration in those with and without myopia, possibly due to a lack of power 19. The only longitudinal study investigating this relationship found no association between myopia at 15 years of age and previous serum 25[OH]D 3 or total serum 25[OH]D, after adjusting for reported time spent outdoors at age 9 14.…”
Section: Introductionmentioning
confidence: 95%